Design of optimized wave-optical spheroidal nanostructures for photonic-enhanced solar cells. (August 2016) - Mendes, Manuel J.; Araújo, Andreia; Vicente, António; Águas, Hugo; Ferreira, Isabel; Fortunato, Elvira; Martins, Rodrigo
Abstract: The interaction of light with wavelength-sized photonic nanostructures is highly promising for light management applied to thin-film photovoltaics. Several light trapping effects come into play in the wave optics regime of such structures that crucially depend on the parameters of the photonic and absorbing elements. Thus, multi-parameter optimizations employing exact numerical models, as performed in this work, are essential to determine the maximum photocurrent enhancement that can be produced in solar cells. Generalized spheroidal geometries and high-index dielectric materials are considered here to model the design of the optical elements providing broadband absorption enhancement in planar silicon solar cells. The physical mechanisms responsible for such enhancement are schematized in a spectral diagram, providing a deeper understanding of the advantageous characteristics of the optimized geometries. The best structures, composed of TiO2 half-spheroids patterned on the cells' top surface, yield two times higher photocurrent (up to 32.5 mA/cm 2 in 1.5 µm thick silicon layer) than the same devices without photonic schemes. These results set the state-of-the-art closer to the theoretical Lambertian limit. In addition, the considered light trapping designs are not affected by the traditional compromise between absorption enhancement versus current degradation by recombination, which is a key technological advantage. Graphical abstract: Highlights: High-index dielectric nanostructures are optimized for wave-optics light trapping. Quasi-ideal broadband absorption enhancement is attained in thin film Si solar cells. The design prevents front photonic elements to increase the cells' recombination. The spectral regimes of advantageous anti-reflection and scattering are identified. Up to 50% efficiency enhancement is determined relative to conventional approaches.